Percepções de professoras sobre formação para a cidadania: um estudo numa escola de ensino fundamental – anos iniciais - Castro, Mariângela Machado de (2022)
This thesis is structured around the question: What is training for citizenship according to teachers' perceptions? Its general objective is to analyze the perceptions of teachers from a public school in the early years of Elementary School about training for citizenship and how this training takes place (or not) in curricular and management practices. The relevance of questioning the type of education that schools promote is highlighted, as they interfere in the construction of a type of citizen-subject. The concept of citizenship is related to different world visions, which can take on conflicting connotations. Due to its intrinsic relationship with education, the school reality can be seen from different perspectives, each corresponding to a conception of student-citizen formation. In this research, two opposing and conflicting theoretical perspectives were defined to analyze the concept of citizenship and its relations with the concepts of curriculum and management: the neoliberal/managerialist and the democratic/emancipatory. By advocating in favor of approaching these three concepts in the second perspective, we bet on the articulation between curriculum – conceived as a process and praxis – and democratic management to guide the possibilities of transformation in the school environment. The research, of a qualitative nature, was developed in a public school in the early years of Elementary School in the city of São Carlos/SP. The steps for data construction included application of a form and conducting interviews; data analysis was performed using content analysis. Regarding the results, the participants revealed that they did not have precise ideas about the concept of citizenship, nor had they thought about this topic until the moment of the interview. It is noteworthy the fact that they understand citizenship restricted to the domain of personal relationships. Therefore, the formation of students for citizenship would be guided by the learning of values/principles and would happen “all the time” at school through these relationships, with the teacher as the main mediator. Furthermore, this formation would take place beyond the specific contents of the curricular components, within the scope of the hidden curriculum, being dealt through conversations with the students. Such training would appear, then, as a by-product of the educational action. The interviewees emphasize the importance of the management team in the formation of school actors for citizenship, claiming that this formation is focused on school practices. Elements that denote a more neoliberal/managerial perspective are identified in their speeches, and they also present aspects of the discourses disseminated by the curricular texts and of “common sense”. There is allusion to an inactive and conformist citizenship since their perceptions are centered on the understanding that students should only incorporate certain values to be integrated into society. The announcement of curricular and management practices that promote democratic and emancipatory aspects in the formation of students for citizenship was not identified. However, it is considered that this does not fall under the responsibility of the teachers, since they did not have specific formation on the subject and, still, the school institution itself does not put it precisely in its pedagogical proposal. Through this study, the aim is to contribute academically to the production of knowledge about formation for citizenship by different professionals working in public schools, within the scope of curricular and management processes. The social contribution of the research, on the other hand, is to promote debate in the school space on the introduction of the theme of citizenship in the curriculum and management, to forming the students in the emancipatory perspective of the subject-citizen.